Integración de estándares de accesibilidad, legibilidad y usabilidad para portales web de acuerdo a las leyes vigentes en el Ecuador. - Tillaguango Pintado, Noemi Floreslinda (2015)
The present titration’s work was made through a recompilation and analysis of information, with the objective to develop a “Proposal of technical rules about accessibility, legibility and usability to web portals from Ecuador”, according to laws in our country, in order to offer a basic, simple and useful document which help to designers, webmasters and developers to create accessible, useful and legible web portals. It was made an analysis of rules, documents published by official organisms of normalization (national or international, as: AENOR, INEN, NTC, Global International and ISO), and also for those published by international consortiums of reference (especially web consortium W3C). The main part of this project of titration is the analysis of active laws in Ecuador; according to posed problem, which is detailed based on 3 themes (culture, language and access to information). The application of these technical rules in the elaboration of web portals improves interactivity and navigability of contents through an accessible design and efficient navigation for the user. Finally, it was evaluated 3 portal from Ecuador (educative and governmental)¬; in base to technical rules of the proposal, through web validators (automatic evaluation tools) and it was concluded with an analysis of results obtained determining the level to carry out the raised proposal.